Workload and organizational culture as predictors of job satisfaction and organizational citizenship behavior: Work engagement as a mediating role - David Manafe (Jurnal Fokus Manajemen Bisnis, 2025)
Individuals are the driving force of an organization, exhibiting dynamic workplace behaviors. Understanding these behaviors requires assessing workload, organizational culture, work engagement, job satisfaction, and organizational citizenship behavior. This study aims to enhance existing models by treating workload as an independent variable, positioning job satisfaction and organizational citizenship behavior as predicted outcomes, and incorporating organizational culture as an influencing factor, with work engagement as a mediator. Using a quantitative approach, data were collected through questionnaires distributed to all employees at Department of Population and Civil Registration in Kupang, Indonesia with a final sample of 77 respondents. Data processing was carried out through the Smart PLS 4 software. The results indicate that job satisfaction is positive and significantly influenced by organizational culture and work engagement, while workload has a negative but insignificant effect. Similarly, organizational citizenship behavior is positively impacted by organizational culture and work engagement, whereas workload does not play a substantial role. Work engagement is also confirmed as a mediator in these relationships. These findings highlight the importance of fostering a positive organizational culture and enhancing employee engagement to improve job satisfaction and organizational citizenship behavior. However, as the study focuses on a specific job category, the results may not be generalizable. Future research should explore different job categories and conduct comparative analyses to refine theories on workplace behavior.